Making ethics "First Philosophy": ethics and suffering in the work of Emmanuel Levinas, Elie Wiesel, and Richard Rubenstein - Anderson, Ingrid Lisabeth (2016)
This dissertation examines the ethical systems created in response to the crisis of the Holocaust by Emmanuel Levinas, Elie Wiesel and Richard Rubenstein. Prior to the Holocaust, European Jewish philosophers grounded ethics in traditional metaphysics. Unlike their predecessors, Levinas, Wiesel and Rubenstein all make ethics "first philosophy" by grounding ethics in the temporal experience of suffering rather than ontology or theology, deliberately rejecting ethical views rooted in traditional metaphysical claims. With varying degrees of success, they all employ Jewish texts and traditions to do so. Their applications of Jewish sources are both orthodox and innovative, and show how philosophical approaches to ethics can benefit from religion. Suffering becomes not only the first priority of ethics, but an experience that simultaneously necessitates and activates ethical response. According to this view, human beings are not blank slates whose values are informed exclusively by culture and moral instruction alone; nor is human consciousness awakened or even primarily constituted by reason, as argued by deontologists. Rather, consciousness is characterized by affectivity and sensibility as interconnected faculties working in concert to create ethical response. This dissertation argues that if what makes ethical response possible is located in human consciousness rather than in metaphysics or culture, a re-orientation of philosophy toward the investigation of human affectivity and its role in ethical response is in order. All three thinkers examined actively resist categorization and repudiate claims that a single philosophical system can be successfully applied to all aspects of life, and this dissertation does not choose one of the three projects examined here as the most persuasive or significant. Instead, it explores how the work of Levinas, Wiesel and Rubenstein might be combined, built upon and expanded to form an ethics that is deeply informed by human experience and makes human and non-human suffering our greatest priorities